Carbon-wrapped Fe–Ni bimetallic nanoparticle-catalyzed Friedel–Crafts acylation for green synthesis of aromatic ketones. Issue 24 (8th November 2021) - Zhang, Hao; Song, Xiaojing; Sun, Hao; Lei, Zhenyu; Bao, Shouxin; Zhao, Chen; Hu, Dianwen; Zhang, Wenxiang; Liu, Jingyao; Jia, Mingjun
Abstract : Fe x Ni1− x @NC efficiently catalyzed Friedel–Crafts acylation for green synthesis of aromatic ketones and exploration of the essence of catalytically active sites. Abstract : Developing highly efficient and durable eco-friendly heterogeneous catalysts for the Friedel–Crafts acylation (FCA) reaction has been a long-term and significant target, yet remains a great challenge. Herein, a series of Fe–Ni alloy nanoparticles (NPs) encapsulated inside N-doped carbon spheres (Fe x Ni1− x @NC) was rationally fabricated by pyrolyzing the Fe–Ni bimetallic metal–organic frameworks (BMOFs-Fe x Ni1− x ) to this end. Various characterization results demonstrated that FeNi alloy NPs (25 nm) covered by a thin carbon shell (5 nm) were uniformly distributed throughout the entire carbon-based composite. A number of oxidized metal species (Fe 3+, Ni 2+ ) are present on the surface of the inner bimetallic core, which should be the main source of catalytically active centers of the carbon-wrapped metal NP catalysts. The composition-optimized Fe0.8 Ni0.2 @NC with relatively higher positive surface charges exhibited the highest catalytic activity and excellent stability for the acylation of aromatic compounds with acyl chlorides. The density functional theory calculations revealed that the catalytic activity of the Fe x Ni1− x @NC catalysts could arise from the electron transfer, i.e., from the outermost layer of the carbon shell to the inner positively charged Fe-based metal NPs, which can lead to a positive charge distribution (by acting as weak Lewis acid sites) on the external surface of the carbon-encapsulated metal NP catalysts. In this case, the external carbon shell can function as 'chainmail' to transfer the Lewis acidity (positive charge), and also to protect the inner metal core from the destructive reaction environment, thus resulting in the formation of highly efficient and durable FCA catalysts.